Pemanfaatan kecerdasan buatan (artificial intelligence) generatif dalam pengungkapan retorika separatisme: Kajian linguistik forensik pada narasi kebencian etnis - Kusno, Ali (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This research utilizes Generative Artificial Intelligence (AI) as an analytical tool for digital discourse. Its main objective is to identify the rhetorical strategies of separatism and ethnic hate speech against the Javanese people disseminated on social media, particularly on Instagram. Using a qualitative approach and Fairclough's Critical Discourse Analysis (CDA) framework, this study examines how texts containing discriminatory sentiments, emotional sentence constructions, and exclusive symbols are produced and spread in the digital space. In-depth analysis reveals that user interaction patterns accelerate the dissemination of separatist ideas. From a forensic linguistics perspective, these findings underscore the damaging impact of digital rhetoric on social cohesion, with the potential to erode brotherhood and trigger the fragmentation of national identity. This paper argues that hate narratives are not merely linguistic constructions but also social actions that require a multidisciplinary response. The study concludes with specific recommendations, such as the development of counter-narratives based on linguistic evidence, improved digital literacy, and the formulation of public policies that are pro-national unity. This research provides a significant contribution to maintaining national stability amid information disruption.